Formulación de un fluido de perforación de alto rendimiento polimérico en base agua para el bloque CPO-05 de la cuenca de los llanos orientales (2018)
This project arises from the need of the company Halliburton to explore the well Mariposa 1 Block CPO-05 located in the Basin of the Eastern Plains and find the most suitable drilling fluid for this field, since each fluid is unique and characteristic for a specific field. This document analyzes the proposed formulations, looking for a solution to the existing problem at the time of drilling the well Mariposa 1 of Block CPO-05 located in the Eastern Plains Basin, in terms of the stability of the well As depth increases, drilling speeds, swelling of clays, control the damage in the formations, control the reaction of shales, among others, taking into account the regulations and benefits for the company.